Hábitat, abundância e padrão de distribuição espacial de Rivulus giarettai (Teleostei, Rivulidae) - Oliveira, Luciano Elias de (2009)
Rivulus giarettai was recently described and is the first record of a rivulid in tributaries of the left bank of the Paranaíba River, southeastern Brazil. This study describes the habitat, the spatial distribution pattern and the abundance of Rivulus giarettai in lakes and palm swamps at the Municipality of Uberlândia, Minas Gerais. Quantitative data obtained for other species, Phalloceros harpagos (Teleostei, Poecilidae) and tadpoles of H. albopunctatus (Anura, Hylidae) are also presented and used as environmental variables. Quantitative samples were made in plots of 0.25 m2, in June 2004 and July 2008. The correlations between the abundance of R. giarettai and the variables measured were verified. Rivulus giarettai inhabits only sunny palm swamps environments, absent at temporary pools and pasture rivers. Rivulus giarettai and P. harpagos had an aggregated distribution in palm swamps and tadpoles aggregated in lakes and palm swamps. The average densities of R. giarettai, Phalloceros harpagos and tadpoles of Hypsiboas albopunctatus in palm swamps were higher than in lakes. In palm swamps, there was positive correlation between the probability of occurrence of R. giarettai and the quantity of plant substratum. The number of individuals was higher within deeper plots and in those with more quantity of plant substratum. The aggregations of tadpoles and the focal species may be an indirect function of free space availability. The aggregated pattern of P. harpagos may be linked to the formation of shoals. The greater average densities founded at palm swamps may be related to higher densities of predators in lakes and the variables deep and quantity of plant substratum may be linked to provision of micro-habitat for refuge.